Design of UTeM logo-shape wearable antenna for communication application by graphene silver nanocomposites - Ahmad Rifhan Salman; Mohd Muzafar Ismail; Jeefferie Abd Razak; Siti Rosmaniza Ab Rashid (Universitas Ahmad Dahlan, 2022)
Previously, the antenna conductive patch was made of copper, which was costly, susceptible to multi-fading, bulky, environmentally sensitive, and difficult to produce. Because of their exceptional electrical conductivity and superior strength to metal, while remaining versatile, the miracle nanotechnology of graphene has made them a possible candidate to replace uncompromising copper metallic content. As a result, graphene is incorporated into conductive silver nanocomposites in this work. With the microstrip feeding technology, the suggested antenna design features a logo-shaped made of graphene and silver patch on a textile substrate and radiates at 2.45 GHz frequency. The antenna’s total dimensions are 60×60×1.6 mm. The simulation results were generated using computer simulation technology (CST) studio suite program software, which improved antenna properties including far-fields, return loss, and voltage standing wave ratio (VSWR). Wearable antennas are promising and have a bright future, especially with the advent of wireless communication technologies, so this new design is essential for the materials revolution in advanced communication and IR4.0 applications, as well as wireless sensor applications